Book Review: Kieko Obuse. Buddhism and Islam: Mutual Engagements in Southeast Asia and Japan. Leiden; Boston: Brill, 2025. 303 pp. ISBN: 9789004704541. - Ashath, Mohamed (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2025)
The academic study of diverse religious traditions, along with their comparison and evaluation, was significantly influenced by nineteenth-century Christian missionaries who sought to understand the beliefs of the people they aimed to reach. This pursuit led to challenges and defenses of various exclusivist claims within Christianity. So, the typology of religious diversity—Exclusivism, Inclusivism, and Pluralism—was introduced by Alan Race, primarily within the context of Christian engagement with other faiths. Consequently, theories of religious diversity have often emerged from debates surrounding such claims, with discussions continuing within Christian theological discourse. So, these three categories are identified as limited and problematic when applied to the broader comparative study of Buddhism and Islam. Their Christian-centric origins fail to account for the unique theological and historical dimensions of these traditions. Therefore, new approaches and methodologies are necessary to foster a more refined and contextually appropriate understanding of Buddhist-Muslim relations.